2020
DOI: 10.1021/acs.jctc.0c00050
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Relaxation Analysis of Protein GB3 for the Assessment of Side Chain Dynamics Predictions by Current AMBER and CHARMM Force Fields

Abstract: Molecular simulations with seven current AMBER- and CHARMM-based force fields yield markedly differing internal bond vector autocorrelation function predictions for many of the 223 methine and methylene H–C bonds of the 56-residue protein GB3. To enable quantification of accuracy, 13C R1, R2, and heteronuclear NOE relaxation rates have been determined for the methine and stereochemically assigned methylene Cα and Cβ positions. With only three experimental relaxation values for each bond vector, central to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“… 8 Furthermore, for positions exhibiting order parameter values below the rigid limit ( S i 2 = 1), the root-mean-square deviation of the experimental uncertainties in the NMR relaxation measurements was found to closely match the resultant rmsd on the ( S f 2 , S H 2 , S X 2 ) order parameters that were derived from the Monte Carlo analysis of those measurements. 7 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 Furthermore, for positions exhibiting order parameter values below the rigid limit ( S i 2 = 1), the root-mean-square deviation of the experimental uncertainties in the NMR relaxation measurements was found to closely match the resultant rmsd on the ( S f 2 , S H 2 , S X 2 ) order parameters that were derived from the Monte Carlo analysis of those measurements. 7 …”
Section: Resultsmentioning
confidence: 99%
“…While in all cases, the calculation of NMR relaxation values utilizes the full range of the complete autocorrelation function, in statistical analysis of the quality of fit between the order parameter-derived autocorrelation functions and those obtained from the MD trajectories, the standard deviation was calculated starting from 30 ps in recognition of the fact that conformational dynamics that are substantially faster than the 1 H Larmor frequency cannot be adequately characterized by this method. 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common approach to compare MD and NMR relaxation experiments involves calculating order parameters from the simulations and comparing to those extracted from the experiments. The results of such comparisons have shown that while MD simulations generally give a relatively good agreement with order parameters for the backbone amide groups, the agreement for methyl bearing side chains is more variable (Bremi et al, 1997;Skrynnikov et al, 2002;Best et al, 2005;Showalter et al, 2007;Liao et al, 2012;O'Brien et al, 2016;Bowman, 2016;Anderson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison to experiments revealed systematic deviations from simulations with several different force fields, and corrections to the methyl torsion potential were developed based on quantum calculations and shown to increase agreement with experiments ( Hoffmann et al, 2018a , 2020 ). Despite these improvements and a substantial body of work on studies of side chain dynamics ( Lee et al, 1997 ; Palmer III, 1997 ; Ming and Brüschweiler, 2004 ; Cousin et al, 2018 ; Anderson et al, 2020 ), the agreement remains imperfect and further improvements would be desirable.…”
Section: Introductionmentioning
confidence: 99%